Calculation of Half-Metal, Debye and Curie Temperatures of Co2VAl Compound: First Principles Study*Supported by the simulation of Nano Physics Lab center of Kermanshah Branch, Islamic Azad University. (1st May 2015) - Boochani, Arash; Khosravi, Heidar; Khodadadi, Jabbar; Solaymani, Shahram; Sarmazdeh, Masoud Majidiyan; Mendi, Rohollah Taghavi; Elahi, Sayed Mohammad
Abstract: By FP-LAPW calculations, the structural, elastic, Debye and Curie temperatures, electronic and magnetic properties of Co2 VAl are investigated. The results indicate that Ferromagnetic (FM) phase is more stable than Anti-Ferromagnetic (AFM) and Non-magnetic (NM) ones. In addition, C11 -C12 > 0, C44 > 0, and B > 0 so Co2 VAl is an elastically stable material with high Debye temperature. Also, the B/G ratio exhibits a ductility behavior. The relatively high Curie temperature provides it as a favorable material for spintronic application. It's electronic and magnetic properties are studied by GGA+U approach leading to a 100% spin polarization at Fermi level.